Oligarchization, de-Westernization and vulnerability: Media between democracy and authoritarianism in Central and Eastern Europe - Balčytienė, Auksė; Bajomi-Lázár, Péter; Štětka, Václav; Sükösd, Miklós (Tidsskrift for Medier, Erkendelse og Formidling, 2015)
What are the major trends of media change in contemporary Central and Eastern Europe (CEE)? How do these media transformations relate to economic, political, social and cultural currents in the region? After a decade of democratic optimism from the early 1990s to the 2000s, why did democratic media regimes in the region become recently so vulnerable? Why would the level of media freedom and pluralism in the CEE region remain significantly more limited than in Western Europe, despite supposedly shared European values and policies, and EU membership of the countries in the region? What explains variation in the level of media freedom within and across the former communist countries? What are the direct and indirect effects of the global financial crisis on the trends of democratization vs. authoritarianism in CEE? How could eminent newly democratized countries in CEE backslide dramatically to semi-authoritarian hybrid regimes that we usually find in former Soviet Eurasia? How do semi-authoritarian regimes control media in different CEE countries? Also, how could media studies of the region be reinvented to reflect on the shifting geopolitical balance of power, especially the emergence of BRICS, the growing influence of Russia, and the war in Ukraine? What could comparative post-communist media studies add to our analysis and understanding of the new CEE realities? These were some of the questions tackled by a recent public roundtable discussion entitled "Media, Democracy and Authoritarianism in Central and Eastern Europe", held at the Department of Media, Cognition and Communication at the University of Copenhagen on April 24, 2015. Participants included Auksė Balčytienė (Professor of Journalism, and Vice Rector for Public Communication and International Relations, Vytautas Magnus University, Lithuania), Péter Bajomi-Lázár (Professor of Media Communications, and Head of the Institute of Social Science at the Budapest Business School, Hungary), and Václav Štětka (Senior Researcher, Institute of Communication Studies and Journalism, Faculty of Social Science, Charles University, Prague, Czech Republic). The panelists have also been working together in a major research project entitled “Media and Democracy in Central and Eastern Europe” between 2009 and 2013 at the University of Oxford. The roundtable was convened and moderated by Miklós Sükösd (Associate Professor, Department of Media, Cognition and Communication, University of Copenhagen). The event was co-sponsored by the Research Priority Area on "Media and Communications in Transition Societies" at the Department of Media, Cognition and Communication at the University of Copenhagen, and the Journal of Media, Cognition and Communication. Participants were asked to reflect on their recent research and contextualize it among what they consider the most important contemporary issues and trends of media and politics in the CEE region.